Consumer intention in purchasing packaging product among the students at Universiti Malaysia Kelantan (UMK). - Nik Mohd Shamim Nik Mohd Zainordin. (2017)
This study will examine the factor that influence the intention of consumers in purchasing packaging products among students at Universiti Malaysia Kelantan (UMK) at three campus which is at City campus, Bachok campus and Jeli campus. In this research, quantitative approach is used and the simple random sampling is used to choose the respondents of this research which is 367 students of Universiti Malaysia Kelantan (UMK) to collect the data about packaging products. After collect the data from the respondents, the researcher used descriptive analysis, reliability analysis, Pearson correlation analysis and exploratory factor analysis using SPSS to analysis the data. The findings indicated that the consumers‟ intention in purchasing packaging products is based on the design of the wrapper, packaging materials and printed information & color.